The aims of lifelong learning: Age-related effects of training on wages and job security - Julia Lang (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
This paper reports the effects of training participation on wages and perceived job security for employees of different ages. Based on data from the German Socio-Economic Panel, results indicate that only younger workers benefit from training by an increase in wages, whereas older employees worries about losing their job are reduced. This observation can also be explained by the fact that goals of training courses are related to the age of participants. Moreover, I differentiate between workers who permanently and only occasionally participate in training. The results indicate that there seem to be decreasing marginal returns to training with respect to job security.
Keywords: J24; J28; J31; 330